Pengembangan Penilaian Autentik dalam Pembelajaran Berbasis Proyek (Bazar) Pada Mata Kuliah Kewirausahaan - Rusdiyana Rusdiyana; Mohamad Joharudin (FKIP Unswagati, 2020)
AbstractÂ Students of economic education are expected to have expertise in the business world including running an entrepreneur. Authentic assessment such as performance appraisal and project is very good to be applied in entrepreneurship courses, and having a strong relevance with the demands of the 2013 Curriculum. The research method is divided into 2 stages namely preliminary studies and development studies. In the development study the RnD model from Borg and Gall Tang was modified. The preliminary stage includes literature study, preliminary observations, and preparation of authentic assessment instruments. The product result from this research is an authentic assessment instrument in entrepreneurship courses consisting of knowledge assessment, skills assessment, and attitude assessment. This authentic project-based assessment instruments aims to increase accountability in the assessment of entrepreneurship courses and for the subsequent evaluation of learning. Based on the results of the combined validity of the learning evaluation expert and the material expert obtained a percentage of 82.5% which means that the authentic assessment instruments in this entrepreneurship material were said to be feasible so that they could be tested on a limited and broader basis. The reliability test results of the authentic assessment instruments in the realm of attitude amounted to 0.74638429, the realm of knowledge amounted to 0.70102591, and the realm of skills amounted to 0.71549432 meaning the authentic assessment of each item could be said to be reliable.Â Keywords: Assessment Development,Aauthentic, Project Based